Reflecting Teacher Figure Through Personality - Aida Ambarawati (Department of Biology Education, Faculty of Education and teacher Training, Maritime University of Raja Ali Haji, 2020)
Abstract. Education is not only about transfer of knowledge, it is also an attempt to shape one’s personality of characteristics. Personality is a factor that has an important role in the success of teaching and learning conducted by teachers, related to ascpect cognitive, affective, and psychomotor toward their students, so the ideal teacher is needed not only in terms of intellectuals, but also in personality. The research conducted is using literatur study with data obtained from literature review. This article aims to describe and analyze how become the figure of an ideal teacher with a personality that can be a role model for all levels of society, especially students. Armed with the ideal personality competence, teacher can be more flexible in helping the formation of the personality of their students, so that it can help to achieve one of the aims educational, it is to prepare characterized human resources (HR).